The Effect of a Best Practice Advisory on the Utilization and Impact of Palliative Care Consultation in Heart Failure Hospitalizations - Kaitlyn S. Gooding; Vamsidhar V. Naraparaju; Beth Esstman; Dorothy B. Wakefield; Megan Evjen; Ahmed Naseer; Sara Tabtabai (Palliative Medicine Reports)
Background: Few studies examine palliative care consultations (PCC) in acute decompensated heart failure (ADHF) admissions. Prior data suggest that 6% of admitted patients are referred for PCC. This study evaluates the effect of a best practice alert (BPA) embedded in the electronic record on PCC utilization and outcomes. Methods: Patients admitted between May 1, 2020, and June 30, 2022, with ADHF were included. BPA was triggered at admission for patients with ≥3 ADHF admissions in 6 months or PCC during prior admission. Subjects were divided into early PCC (less than three days of admission), late PCC (more than three days), and no PCC. Demographics, BPA utilization, length of stay (LOS), and cost were compared between groups. Results: Of 684 patients, 18% received PCC: 13.1% had early PCC, 5.12% late PCC, and 81.6% no PCC. Early PCC patients were older with more comorbidities. Patients receiving PCC had lower ejection fraction (p = 0.04). Median LOS was longest in the late PCC group (12 days, p ≤ 0.01) and similar in early and no PCC groups (six and five days, respectively) and remained significant in multivariate analysis. White patients were more likely to receive PCC compared with Black and other races. The late PCC group had the lowest readmission rate at 5.7%; 28 of the 35 patients changed their goals of care to hospice, “do not re-hospitalize,” or “do not intubate/do not resuscitate.” Conclusions: PCC may influence therapy for patients with ADHF and reduce the readmission rate. Clinician biases remain despite the utilization of BPA, with a modest effect on PCC utilization.